Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let's find the product of [tex]\((k-9)^2\)[/tex] using the perfect square trinomial rule.
The perfect square trinomial rule states:
[tex]\[ (a - b)^2 = a^2 - 2ab + b^2 \][/tex]
Here, we have [tex]\(a = k\)[/tex] and [tex]\(b = 9\)[/tex]. Let's substitute [tex]\(k\)[/tex] and [tex]\(9\)[/tex] into the formula.
1. Square the first term [tex]\(a\)[/tex]:
[tex]\[ a^2 = k^2 \][/tex]
2. Subtract twice the product of the first and second term:
[tex]\[ -2ab = -2 \cdot k \cdot 9 = -18k \][/tex]
3. Add the square of the second term [tex]\(b\)[/tex]:
[tex]\[ b^2 = 9^2 = 81 \][/tex]
Putting it all together, we get:
[tex]\[ (k - 9)^2 = k^2 - 18k + 81 \][/tex]
Thus, to fill in the blanks in the given product:
- The expanded form of [tex]\((k-9)^2\)[/tex] is [tex]\(k^2 - 18k + 81\)[/tex].
So, the final answers are:
- The product [tex]\((k-9)^2\)[/tex] can also be written as [tex]\(k^2 - 18k + 81\)[/tex].
- The product is [tex]\(k^2 -\ 18k +\ 81\)[/tex].
The perfect square trinomial rule states:
[tex]\[ (a - b)^2 = a^2 - 2ab + b^2 \][/tex]
Here, we have [tex]\(a = k\)[/tex] and [tex]\(b = 9\)[/tex]. Let's substitute [tex]\(k\)[/tex] and [tex]\(9\)[/tex] into the formula.
1. Square the first term [tex]\(a\)[/tex]:
[tex]\[ a^2 = k^2 \][/tex]
2. Subtract twice the product of the first and second term:
[tex]\[ -2ab = -2 \cdot k \cdot 9 = -18k \][/tex]
3. Add the square of the second term [tex]\(b\)[/tex]:
[tex]\[ b^2 = 9^2 = 81 \][/tex]
Putting it all together, we get:
[tex]\[ (k - 9)^2 = k^2 - 18k + 81 \][/tex]
Thus, to fill in the blanks in the given product:
- The expanded form of [tex]\((k-9)^2\)[/tex] is [tex]\(k^2 - 18k + 81\)[/tex].
So, the final answers are:
- The product [tex]\((k-9)^2\)[/tex] can also be written as [tex]\(k^2 - 18k + 81\)[/tex].
- The product is [tex]\(k^2 -\ 18k +\ 81\)[/tex].
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.